Community Service Activities – Education And Screening For Damage Of Facial Skin Hydration Caused By Sun Exposure In Adolescent Boys - Sukmawati Tansil Tan; Ernawati Ernawati; Alexander Halim Santoso; Yohanes Firmansyah; Anggita Tamaro; William Gilbert Satyanegara (Universitas Maritim AMNI Semarang, 2023)
Early counseling and screening activities regarding skin hydration due to sun exposure are community service efforts aimed at increasing male students' understanding of the importance of maintaining skin hydration and protection against sun exposure. This activity is carried out through an educative and practical approach, by combining counseling, demonstrations, and early screening. The results of this activity showed an increase in male students' understanding of the importance of skin hydration and protection against sun exposure. They are becoming more aware of the need to take care of their skin regularly, use sunscreen, and keep their skin moisturised. Positive behavioral changes were seen in the boys' efforts to maintain healthy skin. Counseling and early screening activities regarding skin hydration due to sun exposure provide significant benefits in increasing understanding, changing behavior, and maintaining healthy skin for male students. This activity is an important effort in increasing awareness and protection of skin health among male students.